Multi‐objective planning tool for the installation of renewable energy resources. Issue 13 (1st October 2015) - Bouhouras, Aggelos S.; Sgouras, Kallisthenis I.; Labridis, Dimitris P.
Abstract : This study examines how environmental and socioeconomic criteria affect renewable energy resources (RES) distribution strategic plans regarding national energy policies. Four criteria are introduced with respective coefficients properly formulated to quantify their capacity. Moreover, these coefficients are properly normalised to combine the effect of each criterion under a uniform formulation. The base case scenario in this work considers an initially available capacity of RESs to be equally distributed among the candidate regions. Six scenarios about different prioritisation are examined. The results prove that different prioritisation criteria yield significant variations regarding the assigned regional RES capacity. The proposed algorithm defines optimisation only by terms of predefined prioritisation criteria; each solution could be considered optimal given that the respective installation strategic plan is subject to specific weighted criteria. The advantages of the proposed algorithm rely on its simplicity and expandability, since both coefficients formulation and resizing procedure are easily performed, as well as additional criteria could be easily incorporated in the resizing procedure. Thus, this algorithm could be considered as a multi‐objective planning tool regarding long‐term strategic plans for nationwide RES distribution.